(untitled) (Biological Sciences - PJSIR, 2006)
The association of invertebrates in Ogbe creek with Ipomea aquatica was investigated within the period from 7th September to 30th November, 2001. 167 invertebrates comprising of 19 species were harvested from 73 weeds. Corixa punctata (22.16%) was the most abundant invertebrate on Ipomea aquatica while Gyrinus notator larvae (0.60%) were the least abundant. The roots sheltered the highest number of invertebrates (113), comprising of 12 species recording a species diversity of 5.36 while the stem sheltered the lowest number of invertebrates (10) compris- ing of 3 species with a species diversity of 2.00. The ability of Ipomea aquatica to harbour invertebrates was influ- enced by the morphological form of the plant. The root was the preferred site for the invertebrates because it was a suitable substrate for clinging and nutrient supply.